Rancang Bangun Game Android Untuk Mengenalkan Angka, Huruf, Warna, Suara Binatang Pada Paud - SUGIYARTO, AGENG; , Gunawan Ariyanto., ST. M.Comp Sc., Ph.D; , Dedi Ary Prasetya, S.T (2015)
Early Childhood Education (ECD) is a preschool education is education where children do not enter formal education. Early childhood education can be applied to children aged four to six, which span an early age is a good time to develop the potential and intelligence of children. The development potential of children as directed in that age range will berdampat on his future life, which is in fact at the age of more children to play games, get to know the song or video on a smartphone parents without any learning for the future. On the basis of the "Design Game Android To Introduce Numbers, Colors, Letters, Sounds Animals In early childhood" was designed and built. For that reason the making of this application is that children aged four to six years can enjoy games while learning, because at that age children's memory on the sound and the shape is still good. These applications can run well on a smartphone screen size of 4 inches jellybean android operating system. Existing applications look attractive and can train your memory loss or the familiar form of numbers, colors, letters, animal sounds. A game that is also interesting and easy to understand.